Multi-omics identification and validation of oxidative phosphorylation–related hub genes in schizophrenia - Zhou, Yu; Zhang, Shuang; Liu, Yao-Xia; Dai, Xin; Zhang, Ting; Xu, Xiao-Tao; Deng, Sheng-Nan; Yang, Min-Yan; Fan, Zhen (Frontiers in Genetics, 2025)
IntroductionDysfunction in mitochondrial oxidative phosphorylation (OXPHOS) has been implicated in the pathophysiology of schizophrenia, yet its molecular underpinnings remain poorly defined. In this study, we performed an integrative multi-omics analysis to delineate these molecular signatures.MethodsBulk transcriptomic datasets of schizophrenia patients and controls were obtained from the Gene Expression Omnibus. Differentially expressed genes (DEGs) associated with OXPHOS were identified through a combination of differential expression analysis, single-sample gene set enrichment analysis (ssGSEA), and weighted gene co-expression network analysis (WGCNA). Hub genes were prioritized by machine learning algorithms (LASSO, SVM-RFE, and random forest). These hub genes were validated using an independent dataset and further corroborated by RT-qPCR in an MK-801-induced mouse model. Single-nucleus RNA sequencing (snRNA-seq) was employed to delineate cell type-specific oxidative phosphorylation activity and transcriptional profiles.ResultsTranscriptomic analysis identified 130 DEGs between schizophrenia and controls, significantly enriched in oxidative phosphorylation and mitochondrial respiration pathways. Subsequent ssGSEA confirmed the reduced OXPHOS enrichment scores in schizophrenia. Furthermore, WGCNA uncovered two hub modules significantly associated with OXPHOS, which also showed strong correlations with schizophrenia. Intersecting their 2,609 module genes with 130 DEGs yielded 69 OXPHOS-related DEGs. From these, machine learning prioritized six hub genes, four of which demonstrated strong diagnostic potential and robust correlations with OXPHOS scores. Extending these findings in vivo, MK-801–treated mice exhibited behavioral and neuronal deficits, reduced ATP5A fluorescence intensity, and decreased ATP concentrations; expression of all four hub genes was significantly altered, with three (MALAT1, PPIL3, and ITM2A) concordant with transcriptomic results. Finally, snRNA-seq analysis indicated that OXPHOS is the principal ATP-generating pathway in the brain, with notable enrichment in excitatory neurons and endothelial cells, and further revealed significant correlations of MALAT1, PPIL3, and ITM2A with OXPHOS, consistent with bulk and in vivo observations.ConclusionThis finding suggests a potential link between OXPHOS dysfunction and schizophrenia, with MALAT1, PPIL3, and ITM2A emerging as candidate regulators of this process.